The Elevation of the Grassroots Economy Based on Local Resources to Create High Value for Sales in the Modern Trade Market: A Case Study of Krasang District, Buriram Province, Thailand - Panoram, Preecha; Srisuk, kulganya; Suphakritsuwannakul, Nitiroj; Jantaraj, Bancha (Journal of Ecohumanism, 2024)
The objectives of this research were to study the production problems, the factors influencing the production of community products based on local resources to enhance their value, and the strategies for elevating the grassroots economy based on local resources for sale in the modern trade market. The case study focused on Krasang District, Buriram Province. The sample group consisted of 50 community product entrepreneurs selected by purposive sampling and 100 consumers selected through the Taro Yamane formula. The tools used included questionnaires, and the statistical methods applied were percentage, mean, standard deviation, T-test, and F-test. The research findings revealed that the most common production problem was in the area of modern market sales (4.71), with the most critical issue being the distribution of products to purchasing markets (4.76). The factors influencing the production of community products based on production resources were generally rated at a high level (4.32). When examined in detail, the highest-ranked factor was consumer behavior, particularly the preference for unique, identity-driven products. The second-ranked factor was related to community products, specifically the creation of a brand reflecting the community’s historical identity. Comparisons by gender and education level showed no significant differences in opinions, with statistical significance at the .05 level.